INSTITUTIONS IN THE BROADENING OF TECHNOLOGICAL MODERNIZATION OF UKRAINE - Geyets, Valeriy (Journal of European Economy, 2017)
The article expounds the need of transformational changes in Ukraine by the model «from the planned to market economy», demanding a new institutional format. It would require a transition to a new level of application of institutional factors enabling the transformation of the role of institutions as organizational structures, and relevant regulatory actions that would make it possible to raise the innovation-oriented investments to a new level. Success of transition to innovative investment model of economic growth of Ukraine is determined first of all by how well developed is institutional environment and specific institutions that promote the implementation of the projects of both macro- and microeconomic modernization. It is important at the same time to improve efficiency and to deepen market relations in the institutional environment of business with the goal of accelerated development of productive forces in Ukraine based upon capitalization of the economy. The capitalization should be the foundation of the processes of broadening of the scale of corporatization and should reach such a level of concentration of capital that can sustain the development of one of its most effective institutional forms, which is a modern corporation.